1986
DOI: 10.1002/ana.410190610
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of the cellular infiltrate in multiple sclerosis lesions

Abstract: Immunohistochemical staining of 16 brains post mortem from patients with progressive multiple sclerosis and of two biopsy specimens from patients with acute demyelinating disease was performed using a panel of monoclonal antibodies reactive with T cells and T-cell subsets, B cells, and Ia (HLA-DR) antigens. Lymphocytic perivascular cuffs were most prominent at the edge of active plaques and were occasionally seen in areas with no evidence of demyelination or macrophage infiltration. Perivascular cuffs consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
1
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(179 citation statements)
references
References 51 publications
6
169
1
3
Order By: Relevance
“…[25][26][27][28] This finding is confirmed in the present study. The relative proportions of CD8 ϩ and CD4 ϩ T cells differ between studies, some describing a predominance of CD8 ϩ T cells 25,27,28 and others of CD4 ϩ cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[25][26][27][28] This finding is confirmed in the present study. The relative proportions of CD8 ϩ and CD4 ϩ T cells differ between studies, some describing a predominance of CD8 ϩ T cells 25,27,28 and others of CD4 ϩ cells.…”
Section: Discussionsupporting
confidence: 92%
“…As in previous studies, [25][26][27][28] we found significantly higher densities of T cells especially within perivascular areas of acute lesions (Figure 3A) and active borders of chronic active lesions ( Figure 3C) (2631 Ϯ 521 cells/mm 2 ), but also within inactive lesions ( Figure 3G) and inactive areas of chronic active lesions ( Figure 3E) (1080 Ϯ 208 cells/mm 2 ), than in NAWM ( Figure 3I) and control tissue ( Figure 3K) (495 Ϯ 143 cells/mm 2 , P ϭ 0.01; summarized in Figure 4A). Consistent with this observation, we noted significantly higher densities of IL-17 ϩ T cells within acute lesions ( Figure 3B) and active borders of chronic active lesions ( Figure 3D) (1687 Ϯ 284 cells/mm 2 ) than in NAWM (Figure 3J) and control tissue ( Figure 3L) (333 Ϯ 105 cells/ …”
Section: Il-17 ϩ T Cells Are Associated With Increased Activity In Mssupporting
confidence: 58%
“…The strongest association is conferred by the human leukocyte/Ag locus (8). The inflammatory response present within the demyelinating lesions mainly comprises CD4 and CD8 T cells as well as macrophages (9). The commonly held view is that this response is autoreactive, targeting CNS-derived Ags (10).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…However, clinical studies have reported that anti-CD4 monoclonal antibody therapy in MS patients does not prevent disease (Lindsey et al, 1994;van Oosten et al, 1997). Hence, CD4 + T cells may play a regulatory or modulatory role in this disease, rather than being the principal culprits; and detailed analyses of T lymphocytes in MS, including examination of brain tissue specimens, has determined that the majority of T cells are CD8 + (Booss et al, 1983;Traugott et al, 1983;Hauser et al, 1986a;Hauser et al, 1986b;McCallum et al, 1987). CD8 + T cells are found in MS lesions in the form of clonal populations, consistent with their having been locally expanded in response to a specific antigen (Babbe et al, 2000;reviewed, Steinman, 2001;Neumann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%